2017
DOI: 10.1001/jamaoto.2016.4131
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Subglottic Stenosis

Abstract: Endoscopic surgery for subglottic stenosis is a critical aspect of patient management. Neither surgical technique nor grade of stenosis was seen to alter the surgical intervals. Mitomycin application was associated with an extended time interval between endoscopic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 29 publications
4
73
1
Order By: Relevance
“…Treatment options for high‐grade LTS vary from endoscopic to open‐neck procedures . However, it has been reported that higher grade of stenosis purported a higher probability of its recurrence after endoscopic treatment, independently from the etiology of the stenosis itself .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for high‐grade LTS vary from endoscopic to open‐neck procedures . However, it has been reported that higher grade of stenosis purported a higher probability of its recurrence after endoscopic treatment, independently from the etiology of the stenosis itself .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatments of ISS may include endoscopic procedures, open neck surgery, or tracheostomy, though no optimal management has been established. 15 The endoscopic approach with CO 2laser dilatation is a minimally invasive procedure with improved tolerability and shorter hospital stays and has been recommended as a first-line treatment modality in patients with first presentation of less severe and anatomically simple ISS. 16,17 However, patients are more likely to experience recurrence at rates between 55-80%, 20 thus requiring multiple interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical tracheoplasty is the only definitive treatment option for high, moderate, or severe stenosis whereas endoscopic excision of stenotic segment, bronchoscopic dilatation, and tracheal stenting may be feasible in mild to moderate cases. 7,8 We in this report discuss about the difficulties with prolonged tracheostomy tube in a postoperative cardiac surgical child with critical SGTS and the anticipated problems during his transfer.…”
Section: Introductionmentioning
confidence: 99%